Does intensive explicit grammar instruction make all the difference? - Macaro, E; Masterman, L (Edward Arnold (Publishers) Ltd, 2006)
This paper investigates the effect of explicit grammar instruction on grammatical knowledge and writing proficiency in first-year students of French at a UK university. Previous research suggests that explicit grammar instruction results in gains in explicit knowledge and its application in specific grammar-related tasks, but there is less evidence that it results in gains in production tasks. A cohort of 12 students received a course in French grammar immediately prior to their university studies in order to determine whether a short but intensive burst of explicit instruction, a pedagogical approach hitherto unexamined in the literature, was sufficiently powerful to bring about an improvement in their grammatical knowledge and performance in production tasks. Participants were tested at three points over five months, and the results were compared with a group which did not receive the intervention. Our results support previous findings that explicit instruction leads to gains in some aspects of grammar tests but not gains in accuracy in either translation or free composition. Reasons for these findings are discussed in relation to theories of language development and the limitations of working memory.